The Use of Moodle in Enhancing Students' Motivation - Sri Rosmiana; Ita Sarmita Samad; Mustakim Mustakim (Universitas Muhammadiyah Enrekang, 2020)
Learning Management System (LMS) is currently being gradually integrated into the learning system especially in university level. Some studies have confirmed the good effects of applying the LMS toward the students’ motivation, learning outcome, and the teaching and learning quality. Unfortunately, most of the teaching model used in STKIP Muhammadiyah Enrekang is still in conventional form. Thus, the researcher intends to conduct the research on the use of moodle as one of LMS online platform as a mean of updating the teaching model used in this institution. Consequently, the present study investigated a research question. That is the extent to which the use of moodle affects the students’ motivation. The instruments used to collect the data is interview. The data collection was analyzed through descriptive analysis. The participants are all the second semester students of English education program in STKIP Muhammadiyah Enrekang in academic year 2019/2020. The result shows that the use of moodle can affect the students’ motivation. There are at least 3 reasons can be concluded for this fact. The first reason is the communication features on moodle help students to communicate easily with peers or teachers. The second reason is moodle can be access anywhere and anytime. The third reason is the economical factor.